HUBUNGAN KEBIASAAN SARAPAN DENGAN KEJADIAN ANEMIA PADA REMAJA: Relationship between Breakfast Habits and the Incidence of Anemia in Adolescents - Ayik Nikmatul Laili; Lailatul Rahmawati; Arlina Laowo (Forind Press, 2023)
Anemia is a condition where the body lacks healthy red blood cells or there are red blood cells that cannot function properly. Adolescence is an age that tends to be a lot of activity and requires quite high energy and calories. Insufficient energy and calorie needs will cause various diseases, one of which is anemia in adolescence. Based on the results of the 2018 Basic Health Research, the prevalence of anemia in adolescents is 32%, which means that 3 - 4 adolescents out of 10 adolescents suffer from anemia. The impact of anemia in adolescents can inhibit growth, be susceptible to infectious diseases, reduce body fitness, and can reduce the spirit of learning so that achievement also decreases. The purpose of this study was to determine the relationship between breakfast habits and the incidence of anemia in adolescents at SMP PGRI Semboro Jember East Java. Analytic observational research method using quantitative approach. This research design is cross sectional. The results of the study using the Chi Square test showed that there was a relationship between breakfast habits and the incidence of anemia with a P value of 0.024. Suggestions that can be given are the need for education to students to get used to breakfast in order to avoid anemia. In addition, there needs to be cooperation between teachers and parents to encourage students to have breakfast every day.